Implementation of Hadamard encoding for rapid multisample analysis in liquid chromatography - Siegle, Alexander Florian; Trapp, Oliver (Journal of separation science, 2015)
Multiplexing based on pseudo-binary modulation sequences is known to increase the signal-to-noise ratio. In this work, Hadamard transform multiplexing is used in high-performance liquid chromatography to increase the sample throughput. Using structured modulation sequences to encode and control sample injections in combination with a fitting algorithm to deconvolute the complex data allowed us to evaluate convoluted chromatograms of up to 128 samples containing three and five analytes, respectively, with good accuracy (<2% deviation). In comparison to conventional high-performance liquid chromatography the analysis time could be reduced by 30 and 55%, respectively.
Gesehen am 17.06.2020